F.O.S Membership System Enhancement using Geolocation, Chatbot with user preferences / Muhammad Haikal Mohamad Moslim, Nor Azylia Ahmad Azam and Muhammad Zaim Naziff Mohammad Niza - Mohamad Moslim, Muhammad Haikal; Ahmad Azam, Nor Azylia; Mohammad Niza, Muhammad Zaim Naziff (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The "Enhancement of the F.O.S Membership System" convey addresses key issue identified during staff interviews about the membership points system and customer satisfaction. In addition to being limited to outlet stores, the system's limitations make it difficult for customers to find other F.O.S locations, receive promotional updates, and identify popular products. To overcome these constraints, this paper proposes a web-based online sales information system with geolocation features and a chatbot with user-specific recommendation capabilities. Provide easy access to membership benefits, real-time promotions, and tailored product recommendations to boost customer engagement and loyalty. Goals include system design, development, testing, and user preference-based product discovery. With technology and data analytics, this initiative will improve customer shopping experiences, brand loyalty, and business growth. With its ability to seamlessly bridge online and offline channels, the proposed system gives customers valuable information and personalized interactions. Overall, implementation will improve retail convenience, satisfaction, and engagement while giving F.O.S a competitive edge.